Avaliação da qualidade hídrica na área de ostreicultura da resex Mocapajuba - São Caetano de Odivelas - PA - SILVA, Wilson Jefferson Silva e (2019)
In this context, the development of this work aimed to make a diagnosis of water quality and environmental conditions in the Resex-Mar area of Mocapajuba, and to evaluate if the implemented RESEX-Mar model meets the conditions necessary for an effective decision-making, if the option of collective decision-making and definition of rules by users are pertinent and ecologically viable from the point of view of the perpetuation of natural resources and how they influence the quality of life of fishermen in the municipality of São Caetano de Odivelas, coastal region of the state of Pará, where oysters are grown in the Alto Pereru community, from which the resources necessary for the social reproduction of families are withdrawn. Analyzes of physical and chemical parameters were carried out in the Pereru de Fátima community, located along the Pereru River. From the obtained results, it can be observed that some parameters indicated a possible anthropogenic action on the Pereru river, also it was observed that certain parameters, indicate that the water quality presented by the river can influence the effective congestion of the management of the oyster, as well as the growth, development or reproduction of shellfish.